Coexistence trend contingent to Mediterranean oaks with different leaf habits. Issue 9 (23rd March 2017) - Di Paola, Arianna; Paquette, Alain; Trabucco, Antonio; Mereu, Simone; Valentini, Riccardo; Paparella, Francesco
Abstract: In a previous work we developed a mathematical model to explain the co‐occurrence of evergreen and deciduous oak groups in the Mediterranean region, regarded as one of the distinctive features of Mediterranean biodiversity. The mathematical analysis showed that a stabilizing mechanism resulting from niche difference (i.e. different water use and water stress tolerance) between groups allows their coexistence at intermediate values of suitable soil water content. A simple formal derivation of the model expresses this hypothesis in a testable form linked uniquely to the actual evapotranspiration of forests community. In the present work we ascertain whether this simplified conclusion possesses some degree of explanatory power by comparing available data on oaks distributions and remotely sensed evapotranspiration (MODIS product) in a large‐scale survey embracing the western Mediterranean area. Our findings confirmed the basic assumptions of model addressed on large scale, but also revealed asymmetric responses to water use and water stress tolerance between evergreen and deciduous oaks that should be taken into account to increase the understating of species interactions and, ultimately, improve the modeling capacity to explain co‐occurrence. Abstract : In a previous work we developed a mathematical model to explain the co‐occurrence of evergreen and deciduous oak groups in the Mediterranean region. A simple formal derivation of the model expresses the criteria for a stable coexistence in a testable form linked uniquely to the actual evapotranspiration of forests community. We ascertain whether this simplified conclusion possesses some degree of explanatory power by comparing available data on oaks distributions and evapotranspiration (MODIS product) in a large‐scale survey embracing the western Mediterranean area. Our findings confirmed the basic assumptions of model addressed on large scale, but also revealed other features that may help the understanding of species interactions and, ultimately, improve the modeling capacity to explain co‐occurrence.